EFEKTIVITAS PERAN ORGANISASI KERJA SAMA ISLAM (OKI) DALAM MENURUNKAN KETIMPANGAN EKONOMI DI NEGARA-NEGARA ISLAM - Ardianto, Fetra (BHUVANA: Journal of Global Studies, 2023)
This research is a descriptive research that aims to analyze the effectiveness of the role of the Islamic Cooperation Organization (OIC) in reducing economic inequality in Islamic countries, especially through the trade sector. The data collection method involves analysis of documents and online sources. Furthermore, this study uses qualitative data analysis with a secondary data approach. In this case the theory of international organizational effectiveness by Biermann and Bauer is used as a framework. This research reveals that the OIC has an effective role through institutions such as COMCEC and ICDT, with collaborative efforts and resource allocation through the IDB. Stakeholder involvement, institutional design, and concrete outputs such as the growth of intra-OIC trade and an increase in the GDP of member countries are evidence of the effectiveness of the OIC in reducing economic inequality through the trade sector. Despite facing challenges such as the COVID-19 pandemic, OIC has succeeded in proving its commitment in efforts to reduce economic inequality in Islamic countries in order to achieve more inclusive economic prosperity.